2006
DOI: 10.1128/jcm.44.3.738-742.2006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Spread of Enterohepatic Helicobacter Species in Mice Reared in a Specific-Pathogen-Free Animal Facility

Abstract: Infections with enterohepatic Helicobacter species (EHS) can change the results of animal experiments.However, there is little information about the prevalence of EHS in noncommercial animal facilities. The aim of this study was to investigate the prevalence and the spread of EHS in specific-pathogen-free (SPF) mice. Fecal samples of 40 mouse lines were analyzed for members of the family Helicobacteraceae using a group-specific PCR targeting the 16S rRNA gene. Additional experiments were carried out to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Ϫ/Ϫ mice are particularly susceptible to common specificpathogen free mouse facility infections, particularly Helicobacter, which is very prevalent and is not routinely tested for at most institutions (67). In our K bϪ/Ϫ D bϪ/Ϫ CIITA Ϫ/Ϫ mouse colony, all mice that developed a rectal prolapse were also Helicobacter positive by PCR of feces, similar to findings in IL-10 Ϫ/Ϫ mice (68,69).…”
Section: Ciitasupporting
confidence: 73%
“…Ϫ/Ϫ mice are particularly susceptible to common specificpathogen free mouse facility infections, particularly Helicobacter, which is very prevalent and is not routinely tested for at most institutions (67). In our K bϪ/Ϫ D bϪ/Ϫ CIITA Ϫ/Ϫ mouse colony, all mice that developed a rectal prolapse were also Helicobacter positive by PCR of feces, similar to findings in IL-10 Ϫ/Ϫ mice (68,69).…”
Section: Ciitasupporting
confidence: 73%
“…We also studied the effect of cross-fostering on the eradication of the pathogens. Previous studies of the prevalence of H. hepaticus showed high variation [3,7,10,26], and there have been few studies of the prevalences of MNV and P. carinii. Thus, it is difficult to confirm whether the prevalences of the infected mice in our facility are high or low compared to those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of experimental and wild rodent species have shown that their intestinal mucosa is commonly colonized with one or more of the EHS. The organisms commonly found include H. bilis, H. ganmani, H. hepaticus, H. mastomyrinus, H. muridarum, H. rodentium, H. trogontum and H. typhlonius (Zenner 1999;Goto et al 2000;Nilsson et al 2004;Bohr et al 2006;Comunian et al 2006;Johansson et al 2006;Taylor et al 2007;Wasimuddin et al 2012). There is little evidence to support a pathogenic role for these organisms but rather they form part of the normal intestinal microbiota in immunocompetent animals.…”
Section: Enterohepatic Infectionsmentioning
confidence: 93%